Accessibility facilitators and barriers affecting independent wheelchair transfers in the community. (3rd October 2021) - Koontz, Alicia M.; Bass, Sarah R.; Kulich, Hailee R.
Abstract: Purpose: The purpose of this study is to identify facilitators and barriers to wheelchair transfers in the community and to identify specific places and surfaces in the community where increasing transfer accessibility could enable greater participation. Methods: This study enrolled 112 wheeled mobility device users who completed a survey describing barriers to independent transfers. Descriptive statistics (means, standard deviations, and percentages) were used to report the survey results. Results: The majority of subjects (≥50% of the sample) who were impacted by the following features found them to be helpful while transferring: presence of transfer aids, presence of grab bars, large enough transfer surface size, storage space for a wheeled mobility device (WMD), large amounts of space and clearance for legs and feet, soft surfaces, and enough space next to the transfer surface. Ninety percent (90.5%) felt their participation was limited when surfaces higher than their WMD were encountered. Participants also reported feeling limited in their participation due to lack of transfer accessibility at a variety of community destinations, including medical facilities (35.1%), modes of transportation (38.5–52.1%), pools and hot tubs (45.4%), dressing rooms (50.0%), amusement parks (49.1%), and boating areas (52.1%). Conclusion: Improving accessibility for independent transfers in the community may support greater participation and lead to a better quality of life. Study findings provide insight into changes that would make the built environment more accessible and safer for wheelchair users who independently transfer. Implications for rehabilitation: Transferring independently is one of the most physically demanding tasks for wheelchair users, and physical and environmental factors may affect transferability in the community. Identifying environmental facilitators and barriers to transfers may improve accessibility for wheelchair users, allowing for greater community participation, reduced risk of falls and injuries, and improvements to quality of life.